Relationship study of transformational leadership and psychological empowerment on employees job satisfaction / Norashikin Hussein, Maimunah Mohd Shah and Nasuha Bhasah - Hussein, Norashikin; Mohd Shah, Maimunah; Bhasah, Nasuha (Universiti Teknologi MARA, 2017)
This study aims to determine the relationship between transformational leadership (TL) and psychological empowerment (PE) towards job satisfaction (JS) among employees in an electric company. Both TL and PE are important factors in determining job satisfaction. TL is a stimulating and engaging relationship between leaders and followers. It is adapted to enhance employees’ job satisfaction. While, PE is related to employees’ performances, attitudes and various work behaviors. Data were collected using questionnaires and were analyzed using SPSS. Random sampling technique was applied in the distribution of the questionnaire. 125 cases were analyzed and findings were interpreted accordingly. The results reveal that only one dimension of transformational leadership (i.e., intellectual stimulation) and one psychological empowerment dimension (ie.,meaning) are significantly related to job satisfaction. Further discussion on the results are shared in this paper.